2017
DOI: 10.1016/j.asjsur.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of varicose veins improves venous clinical severity score despite failure of complete closure of the saphenous vein after 1 year

Abstract: In this study, RFA of varicose veins had an initial success rate of 97.7% and a significantly improved patient VCSS at 1 year. Patients with episodic recanalization of the saphenous vein also exhibited an improved VCSS with favorable duplex findings at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
1
14
3
1
Order By: Relevance
“…A study by Jin HY et al of 117 patients with 1 year follow up showed an almost similar results with a success rate of 97.7% and a significant improvement of VCSS in the failure group also. 6 Giuseppe G et al, in a single centre study of 98 patients, had a 95.4% occlusion rate at 6 months follow up with a significant improvement in CEAP score over 6 months. 7 The recovery study showed a significant improvement in VCSS score in RFA limbs correlating to reduced postoperative pain and edema.…”
Section: Discussionmentioning
confidence: 93%
“…A study by Jin HY et al of 117 patients with 1 year follow up showed an almost similar results with a success rate of 97.7% and a significant improvement of VCSS in the failure group also. 6 Giuseppe G et al, in a single centre study of 98 patients, had a 95.4% occlusion rate at 6 months follow up with a significant improvement in CEAP score over 6 months. 7 The recovery study showed a significant improvement in VCSS score in RFA limbs correlating to reduced postoperative pain and edema.…”
Section: Discussionmentioning
confidence: 93%
“…27 This is similar to reports from another retrospective study using prospectively registered data with one year follow up reported in 2017. 28 Approximately 92% of patients were satisfied with the procedures. This was consistent with low pain score (under 2) in both groups and a comparable regret rate.…”
Section: Discussionmentioning
confidence: 95%
“…However, one of the patients had no complaints about venous insufficiency, corroborating the recent publications that have demonstrated ablation of the saphenous vein improves VCSS, despite failing to close it completely. ( 26 ) Recently, the results of the original VNUS closure device to eliminate truncal venous reflux at 15 years were reported, demonstrating excellent long-term technical success in truncal veins with the first-generation device. ( 27 )…”
Section: Discussionmentioning
confidence: 99%